Analisis Transformasi Spasial Akibat Urban Sprawl di Pinggiran Kota Singaraja, Kabupaten Buleleng - I Gede Wyana Lokantara; Farisa Maulinam Amo (Department of Urban and Regional Planning, Diponegoro University, 2021)
The development of an economic activity that occurs in the city center when it is saturated will experience a movement towards the outskirts of the city. Singaraja City, one of the areas that are experiencing development towards the outskirts of the city. The study aims to analyze the development of the outskirts of Singaraja City spatially by looking at the pattern of urban development due to the influence of urban sprawl and the factors that cause it. This study was analyzed using a spatial analysis approach to determine the pattern of urban development and using a socio-spatial analysis approach to identify the factors causing urban sprawl on the outskirts of Singaraja City. On a macro level, Singaraja City and its outskirts experience a pattern of spatial development in the form of leap-frog development that moves from the city center to the west and east, namely Bakti Seraga Village, Banyuasri Village, and Banyuning Village. The factor that causes urban sprawl to occur on the outskirts of Singaraja City is the high desire of the community to change the orientation of agricultural activities into commercial economic activities by opening shops and services to facilitate student needs. These economic growth factors encourage spatial development in the city center and beyond the administrative boundaries of the city to the outskirts of Singaraja City.